IMPLEMENTATION OF CONSTRUCTIVIST LEARNING THEORY IN PANCASILA EDUCATION LEARNING FOR CLASS X MAN 2 BOJONEGORO: Implementasi Teori Belajar Kontruktivisme dalam Pembelajaran Pendidikan Pancasila Kelas X MAN 2 Bojonegoro - Siti Qoridatul Annisa; Neneng Rika Jazilatul Kholidah; Fifi Zuhriah (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The purpose of this study is to ascertain how the Quiz Team learning paradigm is implemented and how it affects students engagement in the Pancasila Education course. The study was carried out using a descriptive method and a quantitative approach at MAN 2 Bojonegoro. Teachers and students in class X served as research subjects, and data was gathered through observation, interviews, and documentation. The results show that the Quiz Team learning model is carried out in three phases: preparation, implementation, and evaluation. During the learning process, students were divided into small groups, encouraged to collaborate, and motivated through quizzes that stimulated their engagement. The findings demonstrate that using the Quiz Team concept increases student engagement, as evidenced by increased participation, enthusiasm, and responsibility during learning activities. In conclusion, the Quiz Team model proves effective in enhancing student engagement in Pancasila Education